A new species of Huarpea Pate, 1947 (Hymenoptera, Sapygidae) from the semiarid region of Brazil - Lopes, Rogério Botion; Moleiro, Henrique Pereira; Lucena, Daercio A. A. (Zootaxa, 2024)
The genus Huarpea is recorded for the ﬁrst time in northeastern Brazil. A new species, H. rotundicornis Lopes, Moleiro & Lucena, sp. nov., is described and illustrated. The new species represents the first record of Huarpea in the Brazilian semiarid region, and the easternmost record of this genus in South America. A revised key for all known species of Huarpea, with illustrations of diagnostic features, as well as geographical distribution maps are also presented.